2017
DOI: 10.1177/0265659017717437
|View full text |Cite
|
Sign up to set email alerts
|

Educators’ perspectives on facilitating computer-assisted speech intervention in early childhood settings

Abstract: Early childhood educators are frequently called on to support preschool-aged children with speech sound disorders and to engage these children in activities that target their speech production. This study explored factors that acted as facilitators and/or barriers to the provision of computer-based support for children with SSD in early childhood centres. Participants were 23 early childhood educators at 13 centres who participated in the Sound Start Study, a randomised controlled trial that examined the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…A more recent randomized controlled trial , using the computer-based intervention, originally proposed by Wren and Roulstone, involved listening and responding to visual and auditory stimuli and was delivered by educators. This study reported no significant differences in speech outcomes between intervention and control groups, with low adherence to implementation protocols (Crowe et al, 2017;McCormack et al, 2017). The lack of coupled speech production and perception practice (i.e., combining input and output intervention procedures) was given as a possible reason for this finding.…”
Section: Comparisons Of Pcc Scores Across Time Pointsmentioning
confidence: 61%
“…A more recent randomized controlled trial , using the computer-based intervention, originally proposed by Wren and Roulstone, involved listening and responding to visual and auditory stimuli and was delivered by educators. This study reported no significant differences in speech outcomes between intervention and control groups, with low adherence to implementation protocols (Crowe et al, 2017;McCormack et al, 2017). The lack of coupled speech production and perception practice (i.e., combining input and output intervention procedures) was given as a possible reason for this finding.…”
Section: Comparisons Of Pcc Scores Across Time Pointsmentioning
confidence: 61%
“…It is possible that under-dosing moderated the effect of PFSS. In follow-up investigations of the current study, the educators were interviewed about their experience implementing PFSS in a preschool setting (Crowe et al, 2016), and comparisons were made regarding the intensity of the intervention as recorded by the educators and the computer (McCormack et al, 2016). As part of these investigations multiple barriers and facilitators to implementation were identified including personal factors (e.g., child engagement with PFSS), environmental factors (e.g., the logistics of implementing PFSS during a busy preschool day), and computer program factors (e.g., program format, varied game durations).…”
Section: Why Did the Intervention Not Work?mentioning
confidence: 99%
“…Some educators worked consistently with the participants, achieving intensity compliance rates over 90%. Some did not adhere to the prescribed intensity (Crowe et al, 2016;McCormack et al, 2016). This variation in intensity may have influenced the result.…”
Section: Limitationsmentioning
confidence: 99%